Frailty and Redemptive Flourishing: Learning Through Lived Experience - Trentham, John David (Christian education journal, 2022)
This article presents an extended meditation exercise on Christian learning through the lived experience of frailty. It was composed at various points of calendar distance from the author's experience of sudden cardiac arrest. The structure of the meditation conforms to a catechetical–doctrinal framework, appealing to didache, didaskalia, and didasko. An original poem by Dan Haase is referenced and included in the appendix.